Trying corporations: why not prosecute?. Issue 2 (3rd April 2019) - Campbell, Liz
ABSTRACT: This article examines whether deferred prosecution agreements (DPAs), which allow prosecutors to negotiate and enter into agreements with corporations to defer or suspend criminal proceedings, can ever be in the public interest as a way of addressing corporate crime. DPAs are seen as quicker, cheaper and more predictable than the conventional criminal trial but raise questions of consistency, proportionality and fairness, as well as the circumvention of conventional criminal justice by corporations. I consider if and how a mechanism for deferring prosecution in this way coheres with the existing scheme of corporate criminal liability, relying on four United Kingdom case studies to demonstrate the array of issues raised by DPAs. I argue that DPAs are both necessitated by but also misconstrued as a way of offsetting problems with corporate criminal liability. Moreover, and paradoxically, while DPAs are introduced in an effort to remedy such issues, they are deployed also to mitigate the inevitable consequences of conviction. DPAs therefore both serve to supplement as well as dilute corporate criminal liability. This is a tension that has to be confronted.